ОСОБЕННОСТИ ВОСПИТАНИЯ НАРКОЗАВИСИМЫХ ДЕТЕЙ РОДИТЕЛЯМИ С МЕЖЛИЧНОСТНОЙ ЗАВИСИМОСТЬЮ - Natalia BURAGA; Anastasia IVANOVA (Moldova State University, 2018)
Целью представленного исследования является выявление особенностей воспитания наркозависимых детей родителями, страдающими межличностной зависимостью, а также разработка и апробирование программы преодоления родителями межличностной зависимости. PARTICULARITIES OF EDUCATION OF DRUG DEPENDENT CHILDREN BY PARENTS WITH INTERPERSONAL DEPENDENCE   The scope of the study is to determine the particularities of educating the drug addicted children by parents with interpersonal dependence and elaborating and approving a program to overcome interpersonal addiction to parents.